It takes two to tango: Income and payroll taxes in progressive tax systems - Victor Amoureux; Elvire Guillaud; Michaël Zemmour (Luxembourg Income Study (LIS), 2019)
The literature on tax systems generally considers each type of tax in a self-contained way, with its own distributive characteristics. While the income tax is considered as a progressive tax, social insurance contributions are seen as being regressive, namely because of ceilings. Using a database of comparative micro-data at the household level (LIS data, 22 OECD countries, 1999-2016 period), supplemented with OECD data on employer contributions, we measure effective tax rates over the entire income distribution. Our results jeopardize the conventional economic wisdom on the role of income and payroll taxes in tax progressivity, and on their respective impact on inequality reduction. We show that, in all countries of our sample, the progressivity of income tax increases as soon as the progressivity of social insurance contributions decreases. This implies that income and payroll tax schedules are not independent. Even more, they act in a complementary way. While payroll tax heavily compress inequalities at the bottom of the income distribution, income tax reduces inequalities at the top.
Keywords: D31; H30; I38; 330; income tax; social insurance contributions; inequality reduction; progressivity